Multiplex Genome-Editing Technologies for Revolutionizing Plant Biology and Crop Improvement - Abdelrahman, Mohamed; Wei, Zheng; Rohila, Jai S.; Zhao, Kaijun (Frontiers in Plant Science, 2021)
Multiplex genome editing (MGE) technologies are recently developed versatile bioengineering tools for modifying two or more specific DNA loci in a genome with high precision. These genome editing tools have greatly increased the feasibility of introducing desired changes at multiple nucleotide levels into a target genome. In particular, clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) [CRISPR/Cas] system-based MGE tools allow the simultaneous generation of direct mutations precisely at multiple loci in a gene or multiple genes. MGE is enhancing the field of plant molecular biology and provides capabilities for revolutionizing modern crop breeding methods as it was virtually impossible to edit genomes so precisely at the single base pair level with prior genome editing tools such as zinc-finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs). Recently, researchers have not only started using MGE tools to advance genome editing applications in certain plant science fields but also have attempted to decipher and answer basic questions related to plant biology. In this review, we discuss the current progress that has been made toward the development and utilization of MGE tools with emphasis on the improvements in plant biology after the discovery of CRISPR/Cas9. Furthermore, on the most recent advancements involving CRISPR/Cas applications for editing multiple loci or genes are described. Finally, insights in the strengths and importance of MGE technology in advancing crop improvement programs are presented.